La privatización de los baldíos nacionales en Costa Rica durante el siglo XIX: Legislación y procedimientos utilizados para su adjudicación - Salas Víquez, José Antonio (1987)
Includes a discussion of legal means of acquiring private ownership of government lands, from 1821 to 1900. Study stresses criteria used to legitimate property and promote agriculture as the key to national economic development. Identifies manifestations of classical and positivist liberalism since the early 19